Empty and entangled: developing an account of metaphysical anti-foundationalism and interdependence - Jaura, Emma (2025)
Western metaphysics has been dominated by forms of foundationalism- views that commit to the existence of something fundamental. I contribute to the growing recent interest in challenging foundationalism, and enquiring into the possibility of alternatives. The alternative that I pursue and defend in this thesis, is a position that I call anti-foundationalist interdependence. This position refrains from commitment to fundamentalia, by holding that all existing things depend on something else for their existence and identity. I work towards developing an account of this kind, by searching for support amongst analytic metaphysics (especially amongst recent work on metaphysical coherentism), Buddhist philosophy (especially amongst the work of Nāgārjuna), and from current physics (especially from Rovelli’s relational interpretation of quantum mechanics). Using insight from these areas to produce a picture of the structure of reality which lacks foundations, serves to fill an important gap in the fundamentality debate.